👤

what are the factors of x3+5x2-x-5


Sagot :

[tex] \: \huge\mathfrak\red{answer} \: [/tex]

= (x – 1)(x + 1)(x – 5).

••••••••••••••••••••••••••••••••••••••••••••••••••

Solution:

Let x – 1 = 0, then x = 1

Substituting the value of x in f(x),

f(x) = x3 – 5x2 – x + 5

= (1)3 – 5(1)2 – 1 + 5

= 1 – 5 – 1 + 5

= 0

∵ Reminder = 0

∴ x – 1 is a factor of x3 – 5x2 – x + 5

Now dividing f(x) by x – 1, we get

(x-1)x3-5x2-x+5¯(x2-4x-5

x3 – x2

– +

______________________

-4x2 – x

– 4x2 + 4x

+ –

_______________________

– 5x + 5

–5x + 5

+ – x

∴ x3 – 5x2 – x + 5

= (x – 1)(x2 – 4x – 5)

= (x – 1)[x2 – 5x + x – 5]

= (x – 1)[x(x – 5) + 1(x – 5)]

= (x – 1)(x + 1)(x – 5).

••••••••••••••••••••••••••••••••••••••••••••••••••

#CarryOnLearning